Digitalization, Competence, and Organizational Support as Determinants of ASN Performance: The Role of Motivational Mediation in Local Government Agencies in Indonesia - Hetty Fitriyah; Zuripal Zuripal (CV. Civiliza Publishing, 2026)
Objective: This study aims to analyze the influence of digitalization, competence, and organizational support on the performance of the State Civil Apparatus (ASN), with work motivation according to mediation variables. The research was conducted at the South Solok Regency Population Control, Family Planning, Women's Empowerment, and Child Protection Office. Design/method/approach: This study uses a quantitative approach with explanatory design and cross-sectional surveys. The research population amounted to 54 ASN. The sampling technique uses total sampling, so that the entire population is used as a respondent. Data were collected through questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. Findings: The results of the study show that digitalization, competence, and organizational support have a positive and significant effect on motivation. Motivation also has a positive and significant effect on the performance of ASN. Directly, digitalization, competence, and organizational support have a positive and significant effect on the performance of ASN. Competency is the most dominant factor in improving the performance of ASN, followed by digitalization and organizational support. The results of the mediation test showed that motivation mediated the influence of competence on the performance of ASN partially. Motivation also mediates the influence of digitalization on ASN performance, but with a weak level of mediation. Organizational support does not have a positive and significant effect on the performance of ASN through motivation. Originality/value: This article contributes to the study of public sector human resource management by integrating digitalization, competence, organizational support, motivation, and performance in one empirical model. This research also presents evidence from local government agencies in Indonesia that are facing the demands of digital transformation and limited human resource readiness.